AN ANATOMIZING OF FIGURATIVE LANGUAGE ACCUSTOMED IN ED SHEERAN SONGS LYRIC - Hanifah Hanifah; Aseptiana Parmawati (IKIP Siliwangi, 2023)
A figurative language is one that employs variety figurative terminology.This study discusses the figurative analysis used in 's songs Ed Sheeran.The objectives of this study to recognize and describe the figure of speech used in Ed Sheeran's music, and to explain in detail the inferred implications in each figure of speech used in Ed Sheeran's songs. The method used in this study was qualitative which data gained was evaluated by the researcher who clarified the meaning’s of figurative language in six Ed Sheeran song’s. After listening to all of the songs, the research discovered that there are six song that have been collected includes the figures of speech by underlining while quoting the lyrics of the song which consists of the six figures of speech. Next group, the words and sentences contain a figure of speech that has certain meanings that to found in six by Ed Sheeran's songs.Several theories and associated sources are used to support the analysis. Keywords: Type of Figurative Language; Type of Meaning; Ed Sheraan Songs’